(untitled) (International conference on multidisciplinary science, 2026)
This study examines the effect of agrochemicals on the growth, development, and main morphological parameters of maize varieties. The article presents the results of experiments using various agrochemical substances (organic and mineral fertilizers, stimulants, etc.). According to the research results, agrochemicals had a positive effect on plant height, stem thickness, grain yield, and root system development. Furthermore, the effectiveness of the applied agrochemicals was analyzed in relation to the varietal characteristics of maize. Based on the experimental data, the most effective types of agrochemicals and their application rates were determined. This work substantiates the possibilities of rational use of agrochemicals in maize cultivation to increase productivity and improve morphological parameters of plants.